The Legal Possition of Vulnarable Adults in the Republic of North Macedonia In-between the Authority of the State and the Family - Ignovska Elena (Faculty of Philosophy – Skopje, 2025)
For a long period, the family laws have been focused on children’s rights, in cluding their right to opinion in matters that concern them. Vulnerable adults have been usually represented by others, while their own autonomy neglect ed. This has changed internationally. Many European family-law scholars con sider the topic of empowerment of vulnerable adults as the most important one in the junction between Family Law and Law on Persons nowadays, espe cially if we have in mind that demographically Europe has an aging popula tion, hence more adults than children. However, there are very scarce discus sions on this topic in the Republic of North Macedonia, where the concepts of deprivation of legal capacity and guardianship are still a threat towards human rights of vulnerable adults. The threat is especially observed towards their equality rights (not to be discriminated against), private and family life rights (the right to make decisions about their own body, medical treatments, reproductive choices, conclusion of marriage, recognition of parenthood etc.), procedural rights (the right to access to court and administrative institutions, the right to express legally valid opinions in such proceedings), political rights (the right to vote) etc. The Convention on Rights of Persons with Disabilities (CRPD) has been signed and ratified by the Republic of North Macedonia, whereas the Hague Conven tion on the International Protection of the Adults has not been signed. The country took serious measures to implement the CRPD. However, there are many complaints by the CRPD Committee and by associations/organizations that protect rights of persons with disabilities about its full implementation, as well as Courts’ decisions confirming discrimination. The objective of this study is to locate possible human rights infringements for vulnerable adults as a matter of policy enshrined in the legal documents and to try to find better solutions for integrating vulnerable adults in the so ciety. The legal position of vulnerable adults in the country will be observed in light of the CRPD and comparatively. The final aim of the study is to shed light on the less represented by themselves and more represented by others in the country and to find modules to improve their legal position in the future.
Keywords: Vulnerable Adults, Human Rights, Family Law, Legal Capacity, Guardianship